Effects of Using the Vibratory Orthosis on Standing Balance in Patients With Parkinson 's Disease - Kamiar Ghoseiri; Ahlam Bavi; Galavij Ghoseiri (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: The authors of this paper hypothesized that vibration stimulation applied by a vibratory orthosis improves balance in patients with Parkinson’s disease (PD). In this study we evaluate this hypothesis. Methods & Materials: Fourteen PD patients (12 male and 2 female) with mean age of 59.9±9.1 (±SD) years were participated in this cross- sectional study. Using Biodex balance system, the overall stability index in two conditions of eyes-open and eyes-close, each with two situations of motors On and motors Off of the vibratory orthosis were evaluated. Analysis of variance and paired t statistics were used separately to determine the existence of difference and to compare mean values of overall stability index in all four test situations. Results: Analysis of variance test showed a significant difference in mean values of overall stability index in all four test situations (P=0.000). The findings of the study showed that balance improved in all situations that compares eyes-open with eyes-close (P=0.000). Balance was better in eyes-open model with motors On rather than motors Off (P=0.013). In eyes-close model balance was lower inmotors On than that of motors Off (P=0.934). Conclusion: A new orthosis in rehabilitation of PD patients was introduced that can promote new ideas in orthotic design and application. Results showed that vibratory orthosis was effective in enhancing balance in PD patients in eyes-open condition. However, in eyes-close condition, we are not sure of its effectiveness.